2011
DOI: 10.1155/2011/342637
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Colitis‐Associated Carcinogenesis

Abstract: Inflammatory bowel disease (IBD) is a group of chronic inflammatory disorders that affect individuals throughout life. Although the etiology and pathogenesis of IBD are largely unknown, studies with animal models of colitis indicate that dysregulation of host/microbial interactions are requisite for the development of IBD. Patients with long-standing IBD have an increased risk for developing colitis-associated cancer (CAC), especially 10 years after the initial diagnosis of colitis, although the absolute num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 216 publications
(230 reference statements)
1
78
0
1
Order By: Relevance
“…The early detection of premalignant and malignant lesions remains the best means of reducing the risk of mortality from colorectal cancer (2,3). The use of animal models allows the design of novel methods to screen for early signs of colon cancer (17,18). These models will expand our understanding of the mechanisms underlying tumor formation and may be useful to identify novel response indicators that are correlated with the early stages of tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The early detection of premalignant and malignant lesions remains the best means of reducing the risk of mortality from colorectal cancer (2,3). The use of animal models allows the design of novel methods to screen for early signs of colon cancer (17,18). These models will expand our understanding of the mechanisms underlying tumor formation and may be useful to identify novel response indicators that are correlated with the early stages of tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models of colitis-associated tumors for the study of cancer prevention and early detection have been reported (17,18). The oral administration of dextran sulfate sodium (DSS) to mice has been revealed to induce colonic inflammation that is clinically and histologically similar to UC (19).…”
Section: Introductionmentioning
confidence: 99%
“…24,25 This protocol is based on the use of the mutagenic agent, AOM, which exerts colonotropic carcinogenicity. WT and Il10 −/− mice on 129/SvEv genetic background reared and housed in the same room were allowed to age to 10 weeks by which point the Il10 −/− mice develop spontaneous and progressive colitis.…”
Section: Aom/il10 −/− Model Of Cac and Experimental Groupsmentioning
confidence: 99%
“…Patients with long-standing CU have a higher risk of developing colitis-associated cancer (CAC) approximately 8-10 years after the initial diagnosis when compared to the general population [5]. In addition to genomic instability that underlies the process of tumorigenesis, continuous infl ammation in the intestine seems to be a key factor in CAC development since chronic infl ammation is associated with an overexpression of proinfl ammatory cytokines, chemokines, growth factors as well as their receptors, and reactive oxygen species [6,7].…”
Section: Introductionmentioning
confidence: 99%